Arsitektur dan Fungsi Sosial Masjid Jami' Tegalsari Jetis Kabupaten Ponorogo - Ulil Ulfia Husnawati; Muzaiyana; Nuriyadin (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2022)
Abstract: This study aims to find out (1) the history of the establishment of the Jami' Tegalsari Jetis Mosque, Ponorogo Regency (2) the Social Function of the Jami' Tegalsari Jetis Mosque, Ponorogo Regency (3) The Architecture of the Jami' Tegalsari Jetis Mosque, Ponorogo Regency. This study uses a historical approach and a cultural approach by Koentjaraningrat, which states that architectural works are one of the most concrete forms of culture. The historical approach is used to describe the history and development of the Tegalsari Ponorogo Jami Mosque. There are two theories used to facilitate this research, namely, the theory of Continuity and Change and the functional theory. The meaning analysis is used in research to reveal and describe symbols and symbols that act as language in architecture. While the method used in this study is the historical method with heuristic, verification, interpretation, and historiographical stages. The results of the data analysis can be concluded that (1) the Tegalsari Ponorogo Jami Mosque was founded in 1724 AD by Kyai Ageng Muhammad Besari. This mosque has undergone various developments in terms of buildings which are seen regularly from 1978 until now. (2) Historically the Tegalsari Ponorogo Jami Mosque has had a social function for people's lives as one of the efforts to prosper the mosque. (3) In the architecture of the Tegalsari Ponorogo Jami Mosque there are meanings and cultural elements that accompany the beauty of the mosque building. The cultural elements are Javanese architectural culture and Middle Eastern architectural culture. Keywords: Architecture, social function, Tegalsari masque